2019
DOI: 10.1016/j.molp.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Auxin EvoDevo: Conservation and Diversification of Genes Regulating Auxin Biosynthesis, Transport, and Signaling

Abstract: The phytohormone auxin has been shown to be of pivotal importance in growth and development of land plants. The underlying molecular players involved in auxin biosynthesis, transport, and signaling are quite well understood in Arabidopsis. However, functional characterizations of auxin-related genes in economically important crops, specifically maize and rice, are still limited. In this article, we comprehensively review recent functional studies on auxin-related genes in both maize and rice, compared with wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 236 publications
3
86
0
1
Order By: Relevance
“…Relative expression analysis showed that these genes were transcriptionally elevated in transgenic Arabidopsis plants, suggesting that they may be targets of TaSNAC8‐6A (Figure e). While in TaSNAC8‐6A transgenic wheat lines, root transcriptome analysis revealed significant up‐regulation of several auxin transporter genes and the auxin polar transport pathway were highly enriched (Figure c; Figure S9c; Table S6), in agreement with the known mechanisms of auxin translocation (Lavenus et al , ; Matthes et al , ). Our data also revealed similar up‐regulation of several wheat homologs of canonical auxin signal transduction genes, such as ARFs, EINs and Aux/IAA (Figure c; Figure S9c; Table S6).…”
Section: Discussionsupporting
confidence: 64%
“…Relative expression analysis showed that these genes were transcriptionally elevated in transgenic Arabidopsis plants, suggesting that they may be targets of TaSNAC8‐6A (Figure e). While in TaSNAC8‐6A transgenic wheat lines, root transcriptome analysis revealed significant up‐regulation of several auxin transporter genes and the auxin polar transport pathway were highly enriched (Figure c; Figure S9c; Table S6), in agreement with the known mechanisms of auxin translocation (Lavenus et al , ; Matthes et al , ). Our data also revealed similar up‐regulation of several wheat homologs of canonical auxin signal transduction genes, such as ARFs, EINs and Aux/IAA (Figure c; Figure S9c; Table S6).…”
Section: Discussionsupporting
confidence: 64%
“…3b and 4b). This result could explain why shoot regeneration from stems occurred in medium supplemented only with BA [18,19]. However, the addition of auxin into the media greatly decreased bud regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Nine clades of AUX/IAA proteins have been identified (Matthes et al, 2019), allowing for significant subfunctionalization during the evolution of the AUX/IAA family. The majority of Arabidopsis Aux/IAA mutants were first described by their agravitopric root, reduced lateral roots, and/or shorter root phenotypes (Fukaki et al, 2002; Nagpal et al, 2000; Rouse et al, 1998).…”
Section: Discussionmentioning
confidence: 99%